Advances and bottlenecks in microbial hydrogen production. Issue 5 (22nd August 2017) - Stephen, Alan J.; Archer, Sophie A.; Orozco, Rafael L.; Macaskie, Lynne E.
Summary: Biological production of hydrogen is poised to become a significant player in the future energy mix. This review highlights recent advances and bottlenecks in various approaches to biohydrogen processes, often in concert with management of organic wastes or waste CO2 . Some key bottlenecks are highlighted in terms of the overall energy balance of the process and highlighting the need for economic and environmental life cycle analyses with regard also to socio‐economic and geographical issues. Abstract : Biohydrogen production is best achieved by a combination of dark fermentation and photofermentation with the organic acid co‐products of the former fed to the latter via electrodialytic separation. For organic acid waste streams a photofermentation gives a greater energy yield than by producing biogas.